A new genus and species of maimetshid wasps in Lebanese Early Cretaceous amber (Hymenoptera: Maimetshidae) - Engel, Michael S. (Novitates Paleoentomologicae, 2016)
An interesting new maimetshid wasp is described and figured from the Early Cretaceous of Lebanon. Zorophratra corynetes Engel, new genus and species, differs in several important features from all other Maimetshidae and is classified within its own subfamily, Zorophratrinae Engel, new subfamily. A revised key to the genera of the family is provided, and attempts to incorporate all of those taxa known only as compression fossils. The genera of the family are organized into a revised classification, with the tribe Ahiromaimetshini Engel, new tribe, newly recognized within Maimetshinae, and the genus Turgonaliscus Engel, new genus, described for Turgonalus cooperi Rasnitsyn & Jarzembowski (resulting in Turgonaliscus cooperi, new combination).